(untitled) (Damascus University Journal of arts and humanities sciences, 2023)
- Subject: "Revelation of Al-Radhi Al-Astrabady,s comments in his explanation to kafyat Ibn Al-hajeb, on Alam addin Al-Lowraky- Al-Andalusi declarations in his explanation to Al-Juzuliya ". - Aim: Illustration of Al-Radhi accordances to Al-Andalusi declarations, his replying and the judgments which he made. - Illustration of Al-Andalusi,s unilateral concerning opinion and transliteration. - The most important results were that Al-Radhi agreed with Al-Andalusi about twelve matters, and they disagreed in another seventeen matters (ones). - He adopted three judgment on some his declarations. - He showed aunique opinion and a uni- transliteration.